Hutan Halmahera dan Relasi Kuasa Aktor Politik Lokal Halmahera Forest and Power Relations of Local Political Actors - Herman Usman; Syarifuddin Usman; Laily Ramadhany Can; Amrul Djana (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
This study tries to explore the relationship between the Halmahera forest which is inhabited by the Tobelo Dalam people known as O'Hongana Manyawa, inhabiting forest areas, the existence of corporations that control and carry out activities in the forest with the aim of making profits, and the power relations of local political actors. Forests are a source of food for local communities. Halmahera Forest has a long history, in which the shackles of extractive institutions that are deeply entrenched until now have not been fully resolved. Forests have many interests entrenched, especially those with strong economic power and capital. Whereas on the other hand, forests for local communities are the most ideal source to develop food as the final bastion in facing their future. This study tries to collect and explore data through in-depth interviews with local residents, local government, political elites, and groups that have relations with existing locations. The results of this study show that qualitatively, the Halmahera forest which is occupied by indigenous peoples is the most ideal arena for corporates to carry out extractive actions, which local residents cannot afford. Another matter of concern is that forests are also a meeting ground in building power relations between political actors at the central and local levels. Meanwhile, local residents are more of an obstacle to projects in the name of development. They are then considered as people who only give burdens in the name of development, because that must be